Economic foundations for the use of biotechnology to improve farm animal welfare. (September 2019) - Ufer, Danielle; Ortega, David L.; Wolf, Christopher A.
Abstract: Background: Consumer demand for production process traits in food and agricultural products is rapidly increasing. Recent legal measures reflect demand for high animal welfare standards. At the same time, consumers are wary of biotechnology applications in food and agriculture, with calls for natural or organic production across the industry. However, when biotechnologies are applied for the consumer's benefit or address a consumer concern, they become far more acceptable. Scope and approach: This paper explores the economic foundations, challenges and opportunities for consumer acceptance of biotechnology applications in animal welfare, especially gene editing techniques. We review the food economics literature on consumer acceptance of biotechnology to improve animal welfare and discuss the emerging opportunities for future improvements through gene editing using the pork and dairy industries as case studies. We also discuss industry and policy implications of consumer demand for animal welfare and biotechnology in livestock applications. Key findings and conclusions: Understanding the economic foundations of biotechnology use to improve animal welfare aids agricultural producers, scientists and policy makers to make optimal decisions regarding how these important aspects of animal agriculture progress. We find that the future success of a variety of biotechnologies in livestock production will likely depend on consumer acceptance of the resulting products. Animal welfare applications may increase consumer acceptance. Highlights: Consumers generally dislike the use of biotechnology in food products. Market premiums and policies are driving improvements in farm animal welfare. Novel biotechnologies like gene-editing provide opportunities to improve animal welfare. Adoption of gene editing in animal agriculture will depend on consumer acceptance.